RANCANG BANGUN APLIKASI MEDIA PEMBELAJARAN ANAK SEKOLAH MINGGU DENGAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID: (Studi Kasus: GBI Glow Fellowsip Center) - Utami, Yemima Puji; Budi, Akhmad (Jurnal Informatika dan Bisnis, 2022)
Education is one of the things that is very important and very influential in building the nation and country, both formal and informal education. In addition, through education it can create and develop various kinds of technology. Of course, this technology can be used in the field of education to help an effective learning process, not only that, technology is also often used in the fields of business, health, communication, and transportation. One of the technologies that are currently being developed and used as a medium for learning is Augmented Reality. Augmented Reality is a technology that combines or adds computer-generated virtual content with realworld objects. Augmented Reality has 2 methods, namely marker-based augmented reality and marker-less augmented reality. This study provides an overview of how Augmented Reality can be used as a medium for Sunday school learning. The method used to conduct research is Rapid Application Development (RAD). The RAD method has a sequence of processes, namely requirements planning, user design, construction, and cutover. The data for this study were obtained through interviews with Sunday school teachers. The result of this research is AR technology that can produce 3D objects in the form of animals when the scan button on the smartphone screen is clicked. Users also do not need to prepare marker prints because researchers created the application using the marker-less augmented reality method so that it is more efficient. The application of research results is expected to assist Sunday school teachers in teaching stories so that learning is more effective and easy to understand. This is because the application is equipped with 3D animation. In addition, using applications is also very easy just by using an android smartphone. Keyword: Augmented Reality, marker-based augmented reality, marker-less augmented reality, Rapid Application Development